Adoption of virtual and augmented reality in the architecture, engineering, construction, and facilities management (AEC-FM): mixed method analysis of trends, gaps, and solutions - Fathi, Sahand; Sabeti, Sepehr; Shoghli, Omidreza; Heydarian, Arsalan; Balali, Vahid (Frontiers in Built Environment, 2025)
The Architecture, Engineering, Construction, and Facilities Management (AEC-FM) industry is undergoing a transformative phase with the integration of Augmented Reality (AR) and Virtual Reality (VR) technologies. This study investigates adoption trends, challenges, and future potential of AR/VR technologies within the AEC-FM using a mixed-methods approach, including surveys of over 200 industry experts (2018, 2020, and 2023) and thematic analysis of qualitative interviews. Findings reveal initial optimism in 2018 due to technological advancements, followed by tempered expectations as limitations, costs, and implementation challenges became apparent. While adoption has been led by commercial and institutional sectors, recent growth in the industrial sector reflects AR/VR’s value in large-scale, complex projects. Furthermore, perceptions about AR/VR’s future are consistent across age and gender. The study also highlights the industry’s growing preference for outsourcing AR/VR-related tasks and the shift toward cost-effective solutions like Virtual Design and Construction (VDC) technologies reducing the need for internal AR/VR expertise.